The combined effects of high penetration of wind and PV on power system frequency response. (1st May 2015) - Yan, Ruifeng; Saha, Tapan Kumar; Modi, Nilesh; Masood, Nahid-Al; Mosadeghy, Mehdi
Highlights: This paper investigates frequency response with high penetration of wind and PV. The network used in the study is the close representation of South Australia. This network only relies on a few synchronous machines due to wind/PV integration. Different dynamic models are considered including the secondary PV tripping. The secondary PV tripping shows a significant impact on network security. Abstract: To achieve clean energy targets, more renewable generators – mainly wind and photovoltaic (PV) – are being integrated into electricity networks. However, wind and PV are non-synchronous generators to the grid and they traditionally have neither enough inertia response nor governor support to control major frequency excursions under most situations. Currently in South Australia, the combined generation of wind and rooftop PV has nearly reached the level of average demand with minor support through interconnection import. In such a situation it is likely that there may be fewer synchronous machines online for frequency regulation. Under such a scenario, a contingency could produce a more severe frequency excursion, violating in place frequency standards. Further, many distributed PV systems in South Australia may have a default under-frequency protection setting, which could be higher than the under-frequency load shedding (UFLS) threshold. Hence, a moderate generation/import trip may cause a massive secondary PV trip, which may result in an unacceptably low frequency, triggering further load shedding. This will certainly have an adverse impact on network security. A similar issue of secondary PV trip is not restricted to South Australia and may occur in other regions and countries as well. In this paper, a network which loosely represents the Australian National Electricity Market (NEM) is selected and modified to investigate and analyze network frequency response under high non-synchronous machine penetration. This network contains all necessary models for a comprehensive frequency response study, such as synchronous machine, governor, stabilizer and wind generator. The relevant functions such as load frequency relief, PV tripping and load shedding which are essential for frequency response evaluation are established in the approved and well-accepted platform – PSS®E. The results show that low inertia and secondary PV tripping can become serious issues for network frequency regulation and in some situations they can even cause system oscillation and stability concerns.